2019
DOI: 10.1371/journal.pone.0219462
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and degradation of imazapic in soils under different environmental conditions

Abstract: Imazapic is widely used in peanut production, and its residues can cause damage to succeeding crops planted in the following year. The planting area of peanut is large in Henan province. Inceptisol is the main soil type in Henan Province and was used in laboratory experiments that were conducted to investigate imazapic degradation in soil under various environmental conditions. The results indicated that the imazapic degradation rate increased with an increase in temperature, soil pH, and soil moisture, and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The lower dissipation rate of chlorotoluron in S+SMS soil can be explained by the decrease in its leaching through the soil profile because of higher adsorption: K d values as determined by Carpio et al (2020) were 0.773 L kg -1 in S soil and 4.773 L kg -1 in S+SMS (Table S5). High adsorption of chlorotoluron by amended soils leads to a decrease in the bioavailability of the herbicide to be degraded, as reported previously for this herbicide (Kodešová et al, 2012; and for other compounds Su et al, 2019). On the contrary, Rodríguez-Liébana et al ( 2014) found a rapid dissipation of chlorotoluron (DT 50 = 2.4 days) in a field amended soil.…”
Section: Dissipation Kinetics Of Chlorotoluron In Field Unamended and Amended Soilssupporting
confidence: 65%
See 1 more Smart Citation
“…The lower dissipation rate of chlorotoluron in S+SMS soil can be explained by the decrease in its leaching through the soil profile because of higher adsorption: K d values as determined by Carpio et al (2020) were 0.773 L kg -1 in S soil and 4.773 L kg -1 in S+SMS (Table S5). High adsorption of chlorotoluron by amended soils leads to a decrease in the bioavailability of the herbicide to be degraded, as reported previously for this herbicide (Kodešová et al, 2012; and for other compounds Su et al, 2019). On the contrary, Rodríguez-Liébana et al ( 2014) found a rapid dissipation of chlorotoluron (DT 50 = 2.4 days) in a field amended soil.…”
Section: Dissipation Kinetics Of Chlorotoluron In Field Unamended and Amended Soilssupporting
confidence: 65%
“…It is due to abiotic and biotic degradation, loss by volatilization, plant uptake, runoff and/or leaching. Herbicides dissipation in amended soils has been widely studied under laboratory conditions (Barba et al, 2019;Cassigneul et al, 2018;Su et al, 2019). On the contrary, herbicides persistence and dissipation in amended soils have been scarcely studied under field conditions (Cañero et al, 2012;García-Delgado et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The main factor responsible for the dissipation of IMI in the field is microbial degradation (Kraemer et al, 2009;Su et al, 2019). The diversity of microorganisms in the soil is vast; therefore, several soil microorganisms can degrade these herbicides.…”
Section: Dissipation Of Imazapyr and Imazapic In The Soil (Season 201...mentioning
confidence: 99%
“…Therefore, several factors may affect IMI sorption, including soil pH. In low soil pH, these molecules interact strongly with soil particles, slowing the dissipation processes (Gehrke et al, 2021;Su et al, 2019). This fact is due to the amphoteric behavior of IMI, which allows these herbicides to act as weak acids or bases, depending on the pH of the environment in which they are present (Gianelli et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The impact on pesticide degradation of other organic amendments applied to soils has been investigated for the herbicide imazapic under various environmental conditions, including temperature, soil moisture, and soil pH [159]. CM and biogas slurry (BS) have been applied at different rates, and herbicide degradation has been studied at different temperatures (15, 25 and 35 • C), soil moisture content (15%, 40%, 60% and 90%), and soil pH (6.0, 7.0 and 8.0).…”
Section: Effect Of Organic Residues On Pesticide Dissipationmentioning
confidence: 99%